A Proposed Regulatory Framework for Establishing the Saudi Council of Business Engineers (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study proposes the establishment of the Saudi Council of Business Engineers as an independent national professional body dedicated to regulating and developing administrative practice in the Kingdom of Saudi Arabia and aims to build an institutional framework that enhances the professionalism of the business administration discipline and bridges academic knowledge with practical application in light of the institutional and digital transformation witnessed by the Kingdom under Vision 2030 objectives The problem of the study lies in the absence of a professional entity that organizes the business administration profession despite the expansion of its specializations and the growing impact of its practitioners in both the public and private sectors and this absence represents an organizational and institutional gap that affects the quality of administrative outputs and the efficiency of practitioners Therefore the study seeks to provide an organizational and professional framework for establishing a national authority for business engineers that contributes to formalizing the profession unifying its professional and ethical standards improving practitioners’ competencies and linking academic outcomes with labor market needs The study adopts the descriptive analytical and comparative approach through reviewing literature regulations and similar models of Saudi and international professional bodies such as the Saudi Council of Engineers the Saudi Bar Association and the Saudi Organization for Accountants to analyze the gap in the business administration profession and propose a comprehensive founding model for the Saudi Council of Business Engineers The results indicate that the existence of an independent professional body contributes to improving the quality of administrative practices developing national competencies and enhancing governance and transparency in administrative professions It also helps align institutional transformation requirements with labor market demands and supports Vision 2030 objectives related to building a prosperous economy and highly efficient government institutions The study recommends establishing the council by a Cabinet decision under the supervision of a competent governmental body such as the Ministry of Economy or the Ministry of Commerce and adopting a flexible organizational model based on governance sustainability and accountability including the development of professional standards accreditation certificates continuous training and professional development programs that build a professional administrative environment and enhance practitioners’ efficiency in the Kingdom.
Keywords: Saudi Council of Business Engineers; Saudi Professional Authority; Business Engineer; Professional Body; Digital Transformation; Corporate Governance; National Competencies; Saudi Vision 2030